Open-Ocean Minima in δ13C Values of Particulate Organic Carbon in the Lower Euphotic Zone - Close, Hilary G.; Henderson, Lillian C. (Frontiers in Marine Science, 2020)
Extensive studies in the 1980s-1990s led to the characterization of latitudinal variations in sea surface δ13C values of particulate organic carbon (δ13CPOC), and relationships were found with CO2 concentrations, temperature, growth rates, and cell geometries. Surprisingly, no large-scale efforts have been made to describe variations in δ13CPOC values over depth in the water column. Here we compile published examples demonstrating a widespread isotopic pattern in particulate organic carbon of the upper water column. In 51 vertical profiles, δ13CPOC values in the lower euphotic zone on average are 1.4‰ lower than δ13CPOC values in the upper euphotic zone of open ocean settings. In a majority of locations this downward decrease in δ13CPOC values is > 2‰ and up to 5‰, larger than the commonly recognized vertical δ13C variation in dissolved inorganic carbon over the same depths. We briefly review hypotheses and supporting evidence offered by previous studies of individual water columns: The observed patterns could result from vertical differences in photosynthetic growth rates or community composition, biochemical composition of organic matter due to degradation, isotopic disequilibrium within the dissolved inorganic carbon pool, particle dynamics, or seasonal vertical mixing. Coordinated isotopic, biological, and seawater chemistry data are sparse, and consistent drivers of this widespread isotopic pattern are currently elusive. Further work is needed to adequately characterize the environmental conditions coinciding with this pattern, to test its origins, and to determine if the magnitude of upper water column δ13CPOC variations could be a useful marker of upper ocean carbon cycle dynamics.